Analisis Putus Sekolah Penduduk Usia 16-18 Tahun pada Jenjang Pendidikan Menengah di Provinsi Kalimantan Barat Tahun 2024 dengan Discrete-Time Shared Frailty Survival Model - Raiqhan, Kenny Marsell Venezia; Sitorus, Jeffry Raja Hamonangan (Politeknik Statistika STIS, 2025)
Indonesia has committed to increasing secondary education participation through the Wajib Belajar Dua Belas Tahun program. However, many people still do not complete this level, especially in West Kalimantan Province, which recorded the lowest ALS in the Western Region of Indonesia. A significant decline in the high school NPR compared to the previous level also indicates a high dropout rate. This study aims to provide an overview, test variable significance, and analyze dropout risk among people aged 16–18 years at the secondary education level in West Kalimantan Province in 2024. The method used is survival analysis with the discrete-time shared frailty survival model, based on March 2024 Susenas data. Results show that employment status, online learning status, PIP acquisition status, relationship status with head of household, and head of household education level affect school dropout. People who do not receive PIP have the highest dropout risk.